Discovering England's burial spaces: Supporting community heritage. Issue 2 (3rd April 2022) - Pillatt, Toby; Green, Katie; Maxwell, Deborah; Mytum, Harold; Richards, Julian
ABSTRACT: Discovering England's Burial Spaces (DEBS) was a two-year project to develop new tools and resources in support of community-led recording of the above-ground archaeology and tangible heritage of burial spaces. This article focuses on the role community groups had in the process of designing and building parts of the new surveying workflow, paying particular attention to the design of the recording system, the role of new digital tools in supporting surveys, and the barriers that might prevent community groups from archiving their research. While the focus is very much on these issues as they played out within the DEBS project itself, the challenges encountered and lessons learnt have implications for Citizen Science projects more broadly, and for researchers and heritage professionals developing new methodologies and tools.